2020
DOI: 10.1002/jgh3.12403
|View full text |Cite
|
Sign up to set email alerts
|

Peroral cholangioscopy‐guided forceps biopsy versus fluoroscopy‐guided forceps biopsy for extrahepatic biliary lesions

Abstract: Background and Aim Endoscopic retrograde cholangiopancreatography (ERCP)‐related tissue acquisition, including fluoroscopy‐guided forceps biopsy (F‐FB), is a common technique in diagnosing indeterminate biliary lesions. Recently, peroral cholangioscopy (POCS) and POCS‐guided forceps biopsy (POCS‐FB) has also been used for the diagnosis of indeterminate biliary lesions. However, it is uncertain which of those techniques were superior for the diagnosis of extrahepatic cholangiocarcinoma (ECC). We ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…However, some studies did show relatively low sensitivity [19]. Some previous studies have directly compared the diagnostic results of POCS-guided biopsy with those of conventional endoscopic transpapillary biopsy under fluoroscopic guidance (Table 5) [20][21][22]. One study showed that the diagnostic sensitivity of POCS-guided biopsy was significantly better than that of fluoroscopy-guided biopsy [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies did show relatively low sensitivity [19]. Some previous studies have directly compared the diagnostic results of POCS-guided biopsy with those of conventional endoscopic transpapillary biopsy under fluoroscopic guidance (Table 5) [20][21][22]. One study showed that the diagnostic sensitivity of POCS-guided biopsy was significantly better than that of fluoroscopy-guided biopsy [20].…”
Section: Discussionmentioning
confidence: 99%
“…For the acquisition of larger tissue samples, the SpyBite Max biopsy forceps acquire twice the amount of tissue than the SpyBite biopsy forceps[ 9 ]. This is particularly promising given how the diagnostic accuracy of biopsy samples of IBS obtained via the legacy SpyBite biopsy forceps has been hampered by inadequate tissue samples[ 28 ].…”
Section: Choledochoscope Adjuncts and Accessoriesmentioning
confidence: 99%
“…Firstly, choledochoscopy-guided tissue samples are often too small for accurate offsite histopathological examination and thus decrease sensitivity. Adequate tissue acquisition is primarily limited by the technical ability of choledochoscopy forceps jaw[ 28 ]. Other factors include age less than 65 years old (OR = 0.170, 95%CI: 0.044–0.649, P = 0.010) and previous biliary stenting before POC (OR = 0.199, 95%CI: 0.053–0.756, P = 0.017)[ 56 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to aspiration cytology or brush cytology, which may not theoretically provide a sufficient specimen, endobiliary forceps biopsy can be used to collect a histological core specimen that extends deep into the epithelium [ 4 ]. However, a select series that evaluated endobiliary forceps biopsies for malignant biliary strictures revealed sensitivity values of 43–82% and negative predictive values of 31–82% [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. A recent meta-analysis [ 13 ] revealed that the pooled sensitivity and specificity of an endobiliary forceps biopsy for the diagnosis of malignant biliary stricture were 48.1% and 99.2%, respectively.…”
Section: Introductionmentioning
confidence: 99%